2015
DOI: 10.1021/acs.est.5b02736
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated Natural Products in Dolphins: Brain–Blubber Distribution and Comparison with Halogenated Flame Retardants

Abstract: Halogenated natural products (MHC-1, TriBHD, TetraBHD, MeO-PBDEs, Q1, and related PMBPs) and halogenated flame retardants (PBDEs, HBB, Dec 602, Dec 603, and DP) in blubber and brain are reported from five Alboran Sea delphinids (Spain). Both HNPs and HFRs were detected in brain, implying that they are able to surpass the blood-brain barrier and reach the brain, which represents a new finding for some compounds, such as Q1 and PMBPs, MHC-1, TriBHD, TetraBHD, or Dec 603. Moreover, some compounds (TetraBHD, BDE-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 78 publications
8
34
1
Order By: Relevance
“…The lipid content of the brain of mice was 7.00%, much higher than that of liver (1.91%) and muscle tissues (0.59%), in the present study, the lowest concentrations of PBDEs were found in the brains of mice, ducks and chickens. Previous studies suggested that the BBB could be partly responsible for reduced PBDE accumulation in the brain relative to in other tissues (Baron et al, 2015;Voorspoels et al, 2006;Yang et al, 2011). Our results on several vertebrates support this proposal.…”
Section: Pbde Levels In the Brain Compared With Those In Other Tissuessupporting
confidence: 88%
See 2 more Smart Citations
“…The lipid content of the brain of mice was 7.00%, much higher than that of liver (1.91%) and muscle tissues (0.59%), in the present study, the lowest concentrations of PBDEs were found in the brains of mice, ducks and chickens. Previous studies suggested that the BBB could be partly responsible for reduced PBDE accumulation in the brain relative to in other tissues (Baron et al, 2015;Voorspoels et al, 2006;Yang et al, 2011). Our results on several vertebrates support this proposal.…”
Section: Pbde Levels In the Brain Compared With Those In Other Tissuessupporting
confidence: 88%
“…The production of deca-BDEs has ceased in some European countries and in the USA, but they are still used in some developing countries, including China and South Africa (Abafe and Martincigh, 2015;Wan et al, 2013). Despite a declining trend in the levels of PBDEs observed in certain regions, this group of persistent pollutants is still detectable in various environmental media and biotic samples (Baron et al, 2015;Hassan et al, 2013;Yu et al, 2016;Zheng et al, 2015). It has been demonstrated that PBDEs adversely affect the developing brain, resulting in neurodevelopmental disorders (Costa et al, 2014(Costa et al, , 2016Kodavanti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we can see, for all the seven OPFRs, concentrations in brain were always higher than in blubber, showing more affinity for the brain tissue. The same behaviour was found for BDE-153 and hexabromobenzene (Barón et al, 2015). In contrast, levels of other halogenated contaminants were higher in blubber than in brain samples (Corsolini et al, 2014).…”
Section: Tissue Distributionsupporting
confidence: 71%
“…Samples of blubber and brain included in our study were previously also analysed for determining their content on PBDEs and emerging HFRs (Barón et al, 2015). PBDEs levels in blubber ranged from 93.3 to 2045 ng/g lw, with a mean value of 1001 ng/g lw, whereas brain levels ranged from 6.87 to 791 ng/g lw, with a mean value of 205 ng/g lw.…”
Section: Opfrs Vs Pbdesmentioning
confidence: 99%